Crome, Andrew and James McGrath (eds.), ’Time and Relative Dimensions in Faith: Religion and Doctor Who’ - Balstrup, Sarah (Journal for the Academic Study of Religion, 2019)
Crome, Andrew and James McGrath (eds.), Time and Relative Dimensions in Faith: Religion and Doctor Who. London: Darton, Longman & Todd, 2013, pp. 367, ISBN: 9-780-23253-021-6.